Puck drop in the Pacific Northwest : building brand equity for a new professional sport franchise - Davies, Melissa (SAGE business cases, 2019)
This case asks participants to take on the role of a brand consultant, working for the fictional brand management firm, BrandNew, to advise on the branding of a new National Hockey League (NHL) franchise. The consultant will need to identify the strengths and weaknesses in the brand equity for three previous NHL expansion or relocation teams (i.e., Vegas Golden Knights, Winnipeg Jets, Carolina Hurricanes) in order to understand what goes into selecting an effective team name, color scheme, logo, mascot, and how to socially integrate into the host city market. Consultants will then make recommendations for the NHL's next expansion team in Seattle, Washington, so as to build sustained brand equity in the Seattle market.